Polemic against the Waldenses in Expositio Symboli Apostolorum by Johannes Marienwerder - Karczewski, Marek (Studia Warmińskie, 2024)
The main theological work of Johannes Marienwerder (1343–1417) is Expostio Symboli Apostolorum. In it, Johannes included a comprehensive exposition of the truths contained in the Apostolic Symbol. The situation of the Catholic Church at the end of the 14th century was very complex. Many attempts were made to renew the Church. There was growing opposition to its official doctrine and structures. The Waldenses movement was still active in Bohemia and the German-speaking areas. The article presents the topic of Johannes Marienwerder’s polemic against the Waldenses in Expositio Symboli Apostolorum. Three issues are discussed: Johannes Marienwerder’s relationship to the Waldenses – historical background; a general characterization of heresy and heretics; and a critique of the views of the Waldenses.